The Role of Job Satisfaction as a Mediation on Manager Performance: Influenced by Competence and Intelligence - Ajar Siswandono; Djoko Soelistya; Tri Cicik Wijayanti; Suyoto Suyoto (Budapest International Research and Critics University, 2022)
Every company certainly wants to achieve maximum performance. The level of performance in the company is a very important benchmark or persona. And the phenomenon that occurs in frozen food companies is a decrease in Manager level performance in carrying out their functions and duties due to changes in behavior, work environment, competencies of Managers in accordance with educational backgrounds and years of service that support their competencies.”